2017
DOI: 10.1038/srep45751
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan promotes cancer progression and stem cell properties in association with Wnt signaling in colon and hepatocellular carcinoma cells

Abstract: Cancer stem cells (CSCs), a small population of cancer cells, have been considered to be the origin of cancer initiation, recurrence, and metastasis. Tumor microenvironment provides crucial signals for CSCs to maintain stem cell properties and promotes tumorigenesis. Therefore, establishment of an appropriate cell culture system to mimic the microenvironment for CSC studies is an important issue. In this study, we grew colon and hepatocellular carcinoma (HCC) cells on chitosan membranes and evaluated the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…Cancer stem cells play a pivotal role in invasion, metastasis, and chemotherapy resistance . The expression of CD133 and CD44 are indicators of cancer cell stemness . To evaluate the regulation of stemness by KAP1 in NSCLC, we compared sphere formation in KAP1 −/− and WT A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer stem cells play a pivotal role in invasion, metastasis, and chemotherapy resistance . The expression of CD133 and CD44 are indicators of cancer cell stemness . To evaluate the regulation of stemness by KAP1 in NSCLC, we compared sphere formation in KAP1 −/− and WT A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported CSCs to be involved in the stepwise progression of solid tumors including breast, gastric, and cervical cancer . CD44 and activation of WNT, NOTCH1 increases aggressiveness, correlating with progression in colon cancer . CD133 is also associated with enrichment of undifferentiated cells and tumorigenic behavior along with its implication in epithelial dedifferentiation .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a large number of studies concerning the applications of chitosan in cancer therapy. For instance, it is reported that culturing colon and hepatocellular carcinoma cells on chitosan results in enhanced motility, the capacity of self‐renewal, and drug resistance . Moreover, chitosan can probably initiate the canonical Wnt/β‐catenin‐CD44 axis signaling in colon cancer, as well as Wnt‐STAT3 signaling in hepatocellular carcinoma .…”
Section: Chitosan Roles In Diagnosis and Treatment Of Cancersmentioning
confidence: 99%
“…For instance, it is reported that culturing colon and hepatocellular carcinoma cells on chitosan results in enhanced motility, the capacity of self‐renewal, and drug resistance . Moreover, chitosan can probably initiate the canonical Wnt/β‐catenin‐CD44 axis signaling in colon cancer, as well as Wnt‐STAT3 signaling in hepatocellular carcinoma . Chitosan and its NPs have shown antiproliferative effects on breast cancer cell lines, including MDA‐MB‐231 and SK‐BR‐3 .…”
Section: Chitosan Roles In Diagnosis and Treatment Of Cancersmentioning
confidence: 99%